(untitled) (Homiletic, 2023)
Although homileticians have offered various accounts on what leads people to change, this paper argues that helping listeners overcome self-deception is central to human transformation. In so doing, it is not suggested that the listener needs to come to some particular abstract truth, but rather they need help in opening themselves up to the truth of the humanity of the other. Relying on the account of self-deception posited by C. Terry Warner, this paper offers an indirect model that can help listeners make meaningful changes by overcoming the obstacle of self-deception. This preaching model draws on the author’s previous qualitative research in the field of instructional design and builds on homiletic principles discussed in Fred Craddock’s Overhearing the Gospel.